Shape-dependent thermo-plasmonic effect of nanoporous gold at the nanoscale for ultrasensitive heat-mediated remote actuation - Yang, Zhe (2019)
Nanoporous gold (NPG) promises efficient light-to-heat transformation, yet suffers limited photothermal conversion efficiency owing to the difficulty in controlling their morphology for direct modulation of thermo-plasmonic properties. Herein, we showcase a series of shape-controlled NPG nanoparticles with distinct bowl- (NPG-B), tube- (NPG-T) and plate-like (NPG-P) structures for quantitative temperature regulation up to 140 oC in < 1 s using laser irradiation. Notably, NPG-B exhibits a highest photothermal efficiency of 68% which is >12 and 39 percentage points better than other NPG shapes (NPG-T, 56%; NPG-P, 49%) and Au nanoparticles (29%), respectively. We attribute NPG-B’s superior photothermal performance to its >13% enhanced light absorption cross section compared to other Au nanostructures. We further realize an ultrasensitive heat-mediated light-to-mechanical “kill switch” by integrating NPG-B with a heat-responsive shape-memory polymer (SMP/NPG-B). This SMP/NPG-B hybrid is analogous to a photo-triggered mechanical arm, and can be activated swiftly in <4 s simply via remote laser irradiation. Achieving remotely-activated “kill switch” is critical in the case of emergency such as gas leaks where physical access is usually prohibited or dangerous. Our work offers valuable insights on the structural design of NPG for optimal light-to-heat conversion, and create opportunities to formulate next-generation smart materials for on-demand and multi-directional responsiveness.